The 'Best Practice Guide to Conservative Management of Patellofemoral Pain': incorporating level 1 evidence with expert clinical reasoning. Issue 14 (25th February 2015) - Barton, Christian John; Lack, Simon; Hemmings, Steph; Tufail, Saad; Morrissey, Dylan
Abstract : Importance: Patellofemoral pain (PFP) is both chronic and prevalent; it has complex aetiology and many conservative treatment options. Objective: Develop a comprehensive contemporary guide to conservative management of PFP outlining key considerations for clinicians to follow. Design: Mixed methods. Methods: We synthesised the findings from six high-quality systematic reviews to September 2013 with the opinions of 17 experts obtained via semistructured interviews. Experts had at least 5 years clinical experience with PFP as a specialist focus, were actively involved in PFP research and contributed to specialist international meetings. The interviews covered clinical reasoning, perception of current evidence and research priorities. Results: Multimodal intervention including exercise to strengthen the gluteal and quadriceps musculature, manual therapy and taping possessed the strongest evidence. Evidence also supports use of foot orthoses and acupuncture. Interview transcript analysis identified 23 themes and 58 subthemes. Four key over-arching principles to ensure effective management included—(1) PFP is a multifactorial condition requiring an individually tailored multimodal approach. (2) Immediate pain relief should be a priority to gain patient trust. (3) Patient empowerment by emphasising active over passive interventions is important. (4) Good patient education and activity modification is essential. Future research priorities include identifying risk factors, testing effective prevention, developing education strategies, evaluating the influence of psychosocial factors on treatment outcomes and how to address them, evaluating the efficacy of movement pattern retraining and improving clinicians' assessment skills to facilitate optimal individual prescription. Conclusions and relevance: Effective management of PFP requires consideration of a number of proven conservative interventions. An individually tailored multimodal intervention programme including gluteal and quadriceps strengthening, patellar taping and an emphasis on education and activity modification should be prescribed for patients with PFP. We provide a 'Best Practice Guide to Conservative Management of Patellofemoral Pain' outlining key considerations.